The Generation of Mouse and Human Huntington Disease iPS Cells Suitable for In vitro Studies on Huntingtin Function - Szlachcic, Wojciech J.; Wiatr, Kalina; Trzeciak, Marta; Figlerowicz, Marek; Figiel, Maciej (Frontiers in Molecular Neuroscience, 2017)
Huntington disease (HD) is an incurable neurodegenerative disorder caused by expansion of CAG repeats in huntingtin (HTT) gene, resulting in expanded polyglutamine tract in HTT protein. Although HD has its common onset in adulthood, subtle symptoms in patients may occur decades before diagnosis, and molecular and cellular changes begin much earlier, even in cells that are not yet lineage committed such as stem cells. Studies in induced pluripotent stem cell (iPSCs) HD models have demonstrated that multiple molecular processes are altered by the mutant HTT protein and suggested its silencing as a promising therapeutic strategy. Therefore, we aimed to generate HD iPS cells with stable silencing of HTT and further to investigate the effects of HTT knock-down on deregulations of signaling pathways e.g. p53 downregulation, present in cells already in pluripotent state. We designed a gene silencing strategy based on RNAi cassette in piggyBAC vector for constant shRNA expression. Using such system we delivered and tested several shRNA targeting huntingtin in mouse HD YAC128 iPSC and human HD109, HD71 and Control iPSCs. The most effective shRNA (shHTT2) reagent stably silenced HTT in all HD iPS cells and remained active upon differentiation to neural stem cells (NSC). When investigating the effects of HTT silencing on signaling pathways, we found that in mouse HD iPSC lines expressing shRNA the level of mutant HTT inversely correlated with p53 levels, resulting in p53 level normalization upon silencing of mutant HTT. We also found that p53 deregulation continues into the NSC developmental stage and it was reversed upon HTT silencing. In addition, we observed subtle effects of silencing on proteins of Wnt/β-catenin and ERK1/2 signaling pathways. In summary, we successfully created the first mouse and human shRNA-expressing HD iPS cells with stable and continuous HTT silencing. Moreover, we demonstrated reversal of HD p53 phenotype in mouse HD iPSC, therefore, the stable knockdown of HTT is well suited for investigation on HD cellular pathways, and is potentially useful as a stand-alone therapy or component of cell therapy. In addition, the total HTT knock-down in our human cells has further implications for mutant allele selective approach in